Telaah Kontemporer Hermeunetika Double Movement Fazlur Rahman atas Tradisi Islam - Roibin, Roibin; Nurhayati, Ifa (Faculty of Islamic Sciences, Raden Rahmat Islamic University Malang, 2022)
This study will offer 1) the direction of Rahman's study of the Islamic tradition, 2) Rahman's epistemological problems in the study of the Islamic tradition, 3) the study of Rahman's double movement hermeneutics on the Islamic tradition, and 4) Rahman's methodological contribution to the study of the Islamic tradition. This study uses a historical-sociological approach to see in more detail how Rahman examines Islamic traditions from a hermeneutical perspective. The results of this study indicate that first, the direction of Rahman's reading of the Islamic tradition looks very objective, regardless of the subjectivity of the two currents of traditionalist and modernist thought. Rahman did not defend the two currents of thought, each thought received criticism on the one hand, but on the other hand has also received positive appreciation. Second, the epistemological problem that arises in his thinking is the existence of an epistemological pattern of Islamic studies which is both mainstream, extreme right with traditionalist currents and extreme left with modernist currents from Western orientalism circles which are very free in understanding religion. Third, according to the reading of Rahman's theory of double movement hermeneutics at that time, efforts were needed to formalize, permanentize, and verbalize the living sunnah into text form which is now known as hadith. Without this effort, Muslims will lose their identity and experience a historical disconnect. However, the formalization, verbalization, and permanentization of hadith does not mean setting it as an absolute, let alone a rigid rule that rejects the interpretation space of understanding for the religious elite. According to Rahman's most basic view, once the hadith is determined to be absolute, it can no longer be touched by the thoughts of the respective religious elites, and then the living sunnah which has the basic character of nurturing and protecting has been reduced in meaning. Considering this understanding has forced certain situations and conditions to comply with behavior that has been standardized in the form of the hadith. Fourth, Rahman's hermeneutical approach is very significant in the recontextualization of the universal message of teachings inherent in the authoritative sources of each religion. With this approach, maqashidu al-syariah as a religious text teaching message will be actualized according to the breath of the times. Keywords: formalization, hermeneutics, modernist, sunnah, traditionalist